Crystallization of selenomethionyl exo-β-1,3-galactanase from the basidiomycete Phanerochaete chrysosporium - Ishida, Takuya (International Union of Crystallography, 2009)

(untitled)
Exo-β-1,3-galactanase from Phanerochaete chrysosporium (Pc1,3Gal43A) consists of a glycoside hydrolase family 43 catalytic domain and a substrate-binding domain that belongs to carbohydrate-binding module family 35. It catalyzes the hydrolysis of β-1,3-galactan, which is the backbone of the arabinogalactan proteins; the C-terminal carbohydrate-binding module family 35 domain increases the local concentration of the enzyme around β-1,3-galactan by its high affinity for the substrate. To enable phase determination using the multiwavelength anomalous dispersion method, selenomethionyl Pc1,3Gal43A was crystallized at 298 K using the hanging-drop vapour-diffusion method. The presence of selenium in the crystals was confirmed from the X-ray absorption spectrum. The crystals belonged to space group P2(1) and diffracted to 1.8 Å resolution.